Implementasi CRM (Customer Relationship Management) Menggunakan VTiger CRM Pada Perusahaan (Studi Kasus: CV. Maha Sari) - Nyoman Bandem Mahatma Wicaksana (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
To compete and maintain business in a highly competitive era, small and medium enterprises must apply reliable information technology to support customer data, production, and sales as well as marketing management to establish good communication with their customers. One application of information technology that supports small and medium-sized businesses is Customer Relationship Management, known as CRM. This research is in a business model proposal developed from existing business processes, as well as the implementation of a business process proposal on the E-CRM application, namely VTiger CRM. The VTiger CRM application is one of the E-CRM applications that companies can use in their CRM implementation efforts, in which there are various modules that are ready to be used. Several modules owned by the VTiger CRM application are the Campaign, Sales, Order, Invoice, Tickets, Products, Contacts, Reports modules to a module resulting from the customization carried out in this study with the aim of adjusting to the activities carried out by the company, namely the questionnaire module.